Tracheobronchopathia Osteochondroplastica: Two Cases Reports and Review of Literature. Issue 19 (May 2016) - Wang, Na; Long, Fei; Jiang, Shujuan
Abstract : Abstract: Tracheobronchopathia osteochondroplastica (TO) is a relatively rare and benign disease of unknown etiology that is characterized by the accumulation of diffuse cartilaginous and osseous nodules protruding into the anterolateral walls of the trachea and bronchus. However, TO is easy to ignore or misdiagnose due to its nonspecific clinical manifestation. A chest computed tomography (CT) scan with a fiber bronchoscope and pathological biopsy shows the clinical features supporting the ultimate diagnosis. Here, we report 2 misdiagnosed cases of TO and review the literature to further define the diagnosis for clinicians. The first case was a 34-year-old male admitted to the hospital because of recurrent cough and intermittent fever for 10 years. CT scans showed irregular stenosis of the main bronchus and bronchofibroscope showed multiple nodules producing into the lumen. He was initially misdiagnosed of bronchial tuberculosis and received antitubercular agents for nearly half year. Symptoms got no relief and another bronchofibroscope with biopsy tests in our hospital exactly diagnosed of TO. Symptoms were significantly relieved after receiving budesonide associated with antibiotics, etc. Another case was a 46-year-old woman presenting with a history of repeated hoarseness for 8 years and a 2-month exacerbation. She underwent an electronic laryngoscopy 3 times and was diagnosed of laryngitis. Symptoms got no relief after antiinflammatory. CT scan indicated variable degrees of stenosis and calcification of the distal trachea and main bronchi and bronchofibroscope showed dozens of white nodules extruding into the lumen. Histopathologic findings revealed the ultimate diagnosis of TO and antiinflammatories, spasm relievers, and inhaled corticosteroids, showed apparent effects. Poor specificity of TO is observed in clinical manifestation and laboratory inspection. However, a CT scan associated with a bronchoscopy and histopathologic examination greatly contributes to a definitive diagnosis. No specific treatments are recommended, except treatments to alleviate symptoms. Thus, it is of great importance to consider TO when facing unsolved respiratory or external respiratory symptoms to improve the quality of life.